e-Government Acceptance Model During Covid-19 Crisis in Tainan City, Taiwan - Muhammad Iqbal; Helen Dian Fridayani (Institut Pemerintahan Dalam Negeri, 2022)
This research examines the Technology Acceptance Model (TAM) in implementing e-Government during the COVID-19 pandemic in Taiwan. Furthermore, it builds government network infrastructure and develop Internet applications. Internet penetration as the first stage of this development began in 1998 and the second stage intends to promote the different services. The third phase simplifies information services to make them more proactive and accessible to the general population. In the fourth phase, e-government uses more Web 2.0 social networks to offer innovative services that actively address public needs. Finally, the fifth phase is projected to transform Taiwan into a smart nation with people-friendly services, an open, transparent, intelligent government, and evidence-based successful policies. The data were collected through a questionnaire survey on Tainan City’s users of E-Government services. Furthermore, structural model analysis was performed using smartPLS 3.0., while TAM measured the use of e-government. The results showed that the influential factors are perceived ease of use, perceived usefulness, and information quality. The system’s quality has no significant effect on the use of e-government in the era of the COVID-19 pandemic in Tainan City. Keywords: E-Government, Technology Acceptance Model, COVID-19 Abstrak Penelitian ini mengkaji Technology Acceptance Model (TAM) pada implementasi E-Government pada masa krisis covid-19 di Taiwan. Tahapan pengembangan e-government di Taiwan dimulai pada tahun 1998, yang menunjukkan tahap pertama yaitu penetrasi internet. E-government dimaksudkan untuk membangun infrastruktur jaringan pemerintah dan mengembangkan aplikasi internet: tahap kedua adalah tujuan e-government untuk mempromosikan layanan internet pemerintah. Kemudian fase ketiga, e-government, dimaksudkan untuk menyederhanakan layanan informasi menjadi proaktif dan mudah diakses oleh publik. Fase keempat, e-government menggunakan lebih banyak jejaring sosial Web 2.0 untuk menawarkan layanan inovatif yang lebih aktif memenuhi kebutuhan publik. Terakhir, e-government fase kelima diharapkan menjadi Taiwan yang cerdas, memberikan layanan yang nyaman bagi masyarakat, menerapkan pemerintahan yang terbuka, transparan, dan cerdas, serta mengoptimalkan kebijakan efektif berbasis bukti. Data untuk penelitian ini dikumpulkan melalui survei kuesioner pada masyarakat Kota Tainan yang telah menggunakan layanan E-Government. Analisis model struktural dilakukan dengan menggunakan smartPLS 3.0. Hasil penelitian menunjukkan bahwa penggunaan e-government di Kota Tainan dapat diukur dengan menggunakan Theory Acceptance Model. Hasil penelitian menunjukkan bahwa faktor-faktor yang mempengaruhi penggunaan e-government di Kota Tainan adalah persepsi kemudahan penggunaan, persepsi manfaat, dan kualitas informasi. Sementara itu, kualitas sistem tidak berpengaruh signifikan terhadap penggunaan e-government di era pandemi COVID-19 di Kota Tainan. Kata Kunci: E-Government, Model Penerimaan Teknologi, COVID-19